1998
DOI: 10.1080/10473289.1998.10463678
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Household Solid Waste in Kuwait: Magnitude, Type, and Forecasting Models

Abstract: Academia and responsible government authorities have joined hands in a multi-dimensional research project to determine and analyze urban solid waste management in Kuwait in a cost-effective manner. In this study, a random sample of 2,000 households were interviewed, and the 11 private-sector companies responsible for the collection, transport, and disposal of household solid waste were coo rdinated, along with the Kuwait Municipality's Department of Environmental Affairs, to facilitate, expedite, and promote a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In a past study, it was found that an average household in Kuwait generates 2.2 times (8.4 kg) as much as waste generated by a German household per day for the year 1996 (Koushki and Al-Khaleefi, 1998). The average citizen in Kuwait produced 511 kpc of MSW in the year 2008 (Al-Salem and Lettieri, 2009).…”
Section: Msw Generation From Other Asian Nationsmentioning
confidence: 96%
“…In a past study, it was found that an average household in Kuwait generates 2.2 times (8.4 kg) as much as waste generated by a German household per day for the year 1996 (Koushki and Al-Khaleefi, 1998). The average citizen in Kuwait produced 511 kpc of MSW in the year 2008 (Al-Salem and Lettieri, 2009).…”
Section: Msw Generation From Other Asian Nationsmentioning
confidence: 96%
“…A wellinformed and concerned public greatly facilitates program implementation and ensures its success. The reverse holds true for an ill-informed or unconcerned public (Koushki and Al-Khaleefi, 1998). The responses of the sample households to a number of attitudinal questions are shown in Tables 6 and 7.…”
Section: Household Attitudes Regarding the Management Of Hswmentioning
confidence: 96%
“…The mean duration of stay of dwellers was found to be 3.09 years (Table 2). Similar types of socioeconomic parameters were analyzed by Koushki and Al-Khaleefi (1998) in Kuwait. In their study, they placed emphasis on socioeconomic parameters such as family size, family employment, family income, car ownership, education of the head and age of the head.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…South Tarawa and Kiritimati Island have waste generation rates of 0.33 kg/person/day (Naiova, 2000) and 0.25 kg/person/day (Carden and Pulefou, 2000) respectively. This is approximately one quarter that of developed nations such as the United States ( 1.2 kg/person/day) and Kuwait (1.4 kg/person/day) (Koushki and Al-Khaleefi, 1998) and approximately half of those of Western Europe and Japan (Young, 1991). However, the extent of any nation's waste problem lies not in the volume produced but rather in its ability to effectively manage that waste.…”
Section: The Waste Situation In Kiribatimentioning
confidence: 98%